EFFICIENT MANAGEMENT OF THE TIME AND DOSE OF NITROGEN APPLICATION IN LINSEED - Hutra, Danieli Jacoboski; Carvalho, Ivan Ricardo; Silva, Jose Antonio Gonzalez da; Huth, Caroline; Loro, Murilo Vieira; Zimmermann, Cristian; Sangiovo, Jaqueline; Moura, NatÃ£ Balssan (REVISTA DE AGRICULTURA, 2022)
The objective of this work was to identify the agronomic response of the linseed crop subjected to different doses of nitrogen applied at different times throughout the development of the crop. The experimental design used was randomized blocks, organized in a factorial scheme with five nitrogen application times (0, 10, 30, 60 and 90 days after sowing) x five nitrogen doses (0, 30, 60, 90 and 120 kg ha-1) in three replications, totaling 75 experimental units. Nitrogen applications between 23 and 39 days potentiate the height of the first capsule, number of capsules and grain yield. Doses of 45 to 83 kg ha-1 of nitrogen maximize the number of capsules, stem diameter, number of capsules that formed grains and grain yield. The correlation indicates that the grain yield was determined by the final plant population and weight of grains per plant.